Implementación de una máquina trasplantadora de plántulas de tomate riñón para invernaderos - Catucuago Inlago, Darwin Remigio (2022)
The present titling project has as purpose the kidney tomato seedling transplanter implementation for greenhouses, which allows to reduce the transplant time, therefore, the it was used the phase model methodology, what focuses on a systematic procedure to achieve the design appropriate. Which, it was valued parameters that allow the machine model selection, which meets the transplant requirements inside the greenhouses, subsequently, it was the elaborated the design and analysis using the mechanical design software Autodesk Inventor Students, where it was made static and dynamic loads simulations on the structure, axes, bearings and the machine different components to ensure, what its operation and performance is adequate, finally, it concludes with the construction phase.